Local government in the Philippines : a book of readings - Tapales, Proserpina Domingo;Cuaresma, Jocelyn C.;Cabo, Wilhelmina L. (Quezon City, Philippines : Center for local and Regional Governance and National College of Public Administration and Governance, University of the Philippines, 1998)
This books could have been titled Decentralized Governance in the Philippines: a Book of Readings rather than Local Government in the Philippines, because the experience of governance in the Philippines since the passage of the Local Government code of 1991 can be described as a quick change to decentralized governance.
Chapter 1. Decentralization and local government -- Chapter 2. History of local government in the Philippines -- Chapter 3. Organization, structure, powers and personnel system -- Chapter 4. Fiscal administration and local economic development -- Chapter 5. People's Participation in governance -- Chapter 6. Issues in devolution.
Includes bibliographical references.
Keywords: LOCAL GOVERNMENT